Hygroscopicity and CCN activity of atmospheric aerosol particles and their relation to organics: Characteristics of urban aerosols in Nagoya, Japan. Issue 8 (23rd April 2016) - Kawana, Kaori; Nakayama, Tomoki; Mochida, Michihiro
Abstract: The size‐resolved distributions of hygroscopic growth factor g and the ratios of cloud condensation nuclei (CCN) to condensation nuclei of atmospheric aerosols were investigated in Nagoya, Japan. The average of the distributions of g at 85% relative humidity was bimodal. The size‐resolved mean κ derived from g showed an increasing trend with diameter: 0.17–0.33 at 24–359 nm. The κ values calculated from CCN activation curves were 37% higher than those derived from g . Only 9% of the 37% difference is explained by the difference in the κ of inorganics under subsaturated and supersaturated conditions, suggesting a contribution of organics to the remaining 28% difference. The size‐averaged κ of organics ( κ org ) was calculated as 0.14 and 0.19 by two different methods. The number fractions of CCN predicted from the hygroscopicity data over the range of 24–359 nm are loosely consistent with those observed if the size‐ and time‐averaged g is applied to all particles (differences: −30% to +10%). This consistency improves if size‐ and time‐resolved g and g distribution are used (differences: −19% to −3%). Whereas the number fractions of CCN predicted from the composition data are greatly underestimated if organics are assumed to be insoluble (differences: −64% to −45%), they are more consistent if κ org of 0.14 or 0.19 is applied (differences: −10% to +14%). The results demonstrate the importance of the dependence of the g of particles on time and particle size and the hygroscopicity of organics for CCN number concentrations in the urban atmosphere. Key Points: The average of hygroscopic growth factor distributions was bimodal The hygroscopicity parameter κ of organics was estimated to be 0.14–0.19 The details of hygroscopicity are important to CCN number concentrations